Factors Influencing Company Performance - Alya Dewi; Etty Murwaningsari (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2024)
Abstract Purpose – The purpose of this research is to examine and obtain empirical evidence about the factors that influence company performance, namely earnings quality, real earnings management, and information asymmetry. Design/methodology/approach – The sample used in this study consists of 79 non-cyclical consumer sector companies listed on the Indonesian Stock Exchange in 2021 and 2022, with a total sample size of 158. This study employs panel data analysis. Findings – Real earnings management has a significant negative impact on company performance. The quality of earnings and information asymmetry do not have a significant impact on company performance. Research limitations/implications –. This study only utilized a sample of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange, thereby limiting its generalizability.